Neonatal diabetes caused by homozygous KCNJ11 mutation demonstrates that tiny changes in ATP sensititvity markedly affect diabetes risk - Vedovato, N; Cliff, E; Proks, P; Poovazhagi, V; Flanagan, S; Ellard, S; Hattersley, A; Ashcroft, F (Springer International Publishing AG, 2016)
Aims/hypothesis The pancreatic ATP-sensitive potassium (KATP) channel plays a pivotal role in linking beta cell metabolism to insulin secretion. Mutations in KATP channel genes can result in hypo- or hypersecretion of insulin, as in neonatal diabetes mellitus and congenital hyperinsulinism, respectively. To date, all patients affected by neonatal diabetes due to a mutation in the pore-forming subunit of the channel (Kir6.2, KCNJ11) are heterozygous for the mutation. Here, we report the first clinical case of neonatal diabetes caused by a homozygous KCNJ11 mutation. Methods A male patient was diagnosed with diabetes shortly after birth. At 5 months of age, genetic testing revealed he carried a homozygous KCNJ11 mutation, G324R, (Kir6.2-G324R) and he was successfully transferred to sulfonylurea therapy (0.2 mg kg−1 day−1). Neither heterozygous parent was affected. Functional properties of wild-type, heterozygous and homozygous mutant KATP channels were examined after heterologous expression in Xenopus oocytes. Results Functional studies indicated that the Kir6.2-G324R mutation reduces the channel ATP sensitivity but that the difference in ATP inhibition between homozygous and heterozygous channels is remarkably small. Nevertheless, the homozygous patient developed neonatal diabetes, whereas the heterozygous parents were, and remain, unaffected. Kir6.2-G324R channels were fully shut by the sulfonylurea tolbutamide, which explains why the patient’s diabetes was well controlled by sulfonylurea therapy. Conclusions/interpretation The data demonstrate that tiny changes in KATP channel activity can alter beta cell electrical activity and insulin secretion sufficiently to cause diabetes. They also aid our understanding of how the Kir6.2-E23K variant predisposes to type 2 diabetes.